2014
DOI: 10.1155/2014/630970
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine as a Potential Aggravator of Symptomatic Cerebral Vasospasm: Two Cases and Argument for Milrinone Therapy

Abstract: Background. During hypertensive therapy for post-subarachnoid hemorrhage (SAH) symptomatic vasospasm, norepinephrine is commonly used to reach target blood pressures. Concerns over aggravation of vasospasm with norepinephrine exist. Objective. To describe norepinephrine temporally related deterioration in neurological examination of two post-SAH patients in vasospasm. Methods. We retrospectively reviewed two charts of patients with delayed cerebral ischemia (DCI) post-SAH who deteriorated with norepinephrine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It is hypothesized that the activation of sympathetic nerves through hyperthyroidism induces vasospasm. Cerebral arteries are innervated by sympathetic nerves containing noradrenaline and 5-hydroxytryptamine, and excess catecholamine levels or sensitivity due to thyrotoxicosis can lead to vasospasm [11]. Moreover, vascular contractile responses to norepinephrine were greater in large vessels than in small ones [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the activation of sympathetic nerves through hyperthyroidism induces vasospasm. Cerebral arteries are innervated by sympathetic nerves containing noradrenaline and 5-hydroxytryptamine, and excess catecholamine levels or sensitivity due to thyrotoxicosis can lead to vasospasm [11]. Moreover, vascular contractile responses to norepinephrine were greater in large vessels than in small ones [12].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several in vitro studies using a rat model reported discrepant findings, which indicated that HIF inhibition per se has been associated with improved blood-brain barrier 34,35 In contrast, the therapeutic efficacy of MIL infusion with and without intravenous sedation in patients following SAH has been established in several clinical settings including SAH. 6,11,14,[29][30][31][32][33] Thus, the timing, severity, and sustainability of HIF-1α upregulation and its downstream transcriptional effects may also be pursued in translational studies using genetically modified mice [36][37][38] to identify more promising preventive or prophylactic interventions against post-SAH DCI.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, however, the infusion of catecholamines such as noradrenaline and dobutamine may have limited effects and may aggravate cardiac failure due to massive stress hormone release, so‐called ‘catecholamine surge’ or ‘adrenergic storm’ caused by severe acute brain injury . There are also concerns of cerebral vasoconstriction even with the use of the most reliable vasopressor noradrenaline . The phosphodiesterase‐III inhibitor milrinone (MIL) may be an alternative option when inotropes are required but dobutamine is contraindicated due to tachycardia, left ventricular outflow obstruction or neurogenic cardiomyopathies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient's exam improved after starting milrinone and stopping norepinephrine, while the second patient deteriorated clinically in spite of milrinone. Again, hypotension and tachycardia were not mentioned as side effects, and patients did not have preexisting cardiac problems [8].…”
Section: Discussionmentioning
confidence: 99%